Use of biological and сhemical fungicides and biostimulators for potato protection against early and late blights - A. Yu. Ukolova; M. A. Kuznetsova (Овощи России, 2025)
Relevance. Every year, European countries review the list of approved pesticides and ban many of them. At the same time, increased agricultural intensification leads to soil contamination with pesticide residues, which is harmful to environment and human health. In this regard, using of biological solutions and biostimulants in the framework of comprehensive disease and pest control to ensure environmental safety is growing.Methodology. In 2023, field experience was established to evaluate the effectiveness of combined use of fungicide Manfil (mankozeb 800 g/kg) and biofungicide Agat-25K (metabolites of the Pseudomonas aureofaciens strain) with the biostimulator ExcelGrow (Ascophyllum nodosum algae extract) in the control of Phytophthora and Alternaria on susceptible to late blight potato cultivar Arizona and susceptible to early blight potato cultivar Aluett.Results. In the variants of combined use of fungicides with the ExcelGrow biostimulator, there was a significant decrease in the integral indicator of disease development, a significant decrease in the development of diseases compared with the variants of using only fungicides solo, as evidenced by the data of biological efficacy. In the experiment, it was shown for the first time that the use of the ExcelGrow biostimulator with Manfil and Agat-25K preparations increases their biological effectiveness on late blight resistant and susceptible to early blight varieties by up to 12%, additionally increases yields by 1.5-3.5% and demonstrates an increase in the marketability of tubers by 13%, which indicates that ExcelGrow increases the immune status plants, preventing their infection with Alternaria.